2022
DOI: 10.1002/alr.23008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of competing endogenous RNA (ceRNA) crosstalk in eosinophilic chronic rhinosinusitis with nasal polyps

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is one of the most common chronic inflammatory diseases, and has various phenotypes. Although its pathophysiology remains obscure, evidence has shown that dysregulation of noncoding RNAs (ncRNAs) is associated with CRSwNP. ncRNAs in the cytoplasm can act as competing endogenous RNAs (ceRNAs), which are involved in many inflammatory processes. However, the ceRNA crosstalk in CRSwNP is still unclear Methods We investigated expression profiles of messen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Out of the 44 studies investigating the role of non-coding RNAs, most studies investigated miRNAs, and only a few investigated other RNA types such as lncRNAs (40)(41)(42)(43)(44), siRNAs (45), and circRNAs (46,47). Six studies used pre-existing GEO data sets to identify transcriptome-wide miRNA or lncRNA profiles of CRSwNP vs. controls, either exclusively or in conjunction with in vivo studies on CRS subjects (40-42, 44, 46, 48).…”
Section: Non-coding Rna Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 44 studies investigating the role of non-coding RNAs, most studies investigated miRNAs, and only a few investigated other RNA types such as lncRNAs (40)(41)(42)(43)(44), siRNAs (45), and circRNAs (46,47). Six studies used pre-existing GEO data sets to identify transcriptome-wide miRNA or lncRNA profiles of CRSwNP vs. controls, either exclusively or in conjunction with in vivo studies on CRS subjects (40-42, 44, 46, 48).…”
Section: Non-coding Rna Studiesmentioning
confidence: 99%
“…The presence of co-morbid conditions like asthma and allergic rhinitis may influence results of studies, and this may limit our understanding of CRSwNP-specific epigenetic changes. Bioinformatic analyses on pre-existing GEO data sets need to be consistent in including studies that have used the same disease and control tissue, and this has not been done uniformly across these studies (40)(41)(42). In a recent review on epigenetics in CRS, authors have elaborated that several miRNA studies have shown controversial results in whether a specific miRNA was upregulated or downregulated in CRS (18).…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, its expression displays no statistical difference between ECRSwNP and non-ECRSwNP ( Yu et al, 2021b ). Recently, Li and Liu (2022) have found 207 lowly expressed miRNAs and constructed 598 miRNA-mRNA pairs in ECRSwNP. The level of miR-124 decreases in CRSwNP, and is negatively correlated with the expression of aryl hydrocarbon receptor (AHR) and TNF-α, suggesting that miR-124 can influence the differentiation of Th1 and Th17 cells by inhibiting STAT1 and STAT3 activation in the presence of protein inhibitor cytokine signaling 5 (SOCS5) ( Liu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This network showcases six hub differently expressed lncRNAs (MIAT, HOTAIRM1, TSPOAP1-AS1, MSC-AS1, LBX2-AS1, and CARD8-AS1), which interact with miRNAs to regulate the expression of mRNAs in ECRSwNP patients. Among these lncRNAs, CARD8-AS1 and MSC-AS1 can act as ceRNA ( Li and Liu, 2022 ). Recently, Chen et al (2022) have constructed another lncRNA-miRNA-mRNA ceRNA network of CRSwNP, which contains 21 lncRNAs, 8 miRNAs and 8 mRNAs; they proved that the MIAT/miR-125a/IRF4 axis drives the progression of CRSwNP.…”
Section: Introductionmentioning
confidence: 99%